The Contribution of Green Accounting and Green Tax to Tax Avoidance - Ahmad; Sri Luayyi; Muhammad Alfa Niam (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of green accounting and green tax on tax avoidance in energy companies within the coal subsector listed on the IDX during 2022-2024. The study used a quantitaive approach with pur[osive sampling techniques on 20 companies over 3 years. Data was obtained from sustainability and annual reports, then analyzed using multiple linear regression testing in SPSS. The result show that green accounting has a positive and significant effect on tax avoidance, while green tax has no significant effect. Simultaneously, both variables influence tax avoidance, indicating that the implementation of green accounting plays a role in tax avoidance strategies, whereas green tax has not yet been effective. The findings support legitimacy and stakeholder theories, which suggest that companies aim to maintain a sustainable image and manage their tax burdens. Therefore, to enhance the effectiveness of green fiscal policies in improving tax compliance, the government must reinforce environmental tax regulation and oversight. This study combines simultaneous green accounting and green tax analyses of tax avoidance in the energy sector, a previously rare approach in the context of Indonesian companies. Keywords: Green accounting, Green tax, Tax avoidance, Stakeholder Theory, Legitimacy Theory .